1998
DOI: 10.1046/j.1365-2508.1998.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell carcinoma arising in an endometrial polyp

Abstract: This paper describes the appearance of a clear cell carcinoma in an endometrial polyp of an 80‐year‐old patient. The transition between benign and malignant tissue in the polyp was abrupt and did not involve the presence of atypical hyperplasia. Overexpression of p53 protein was detected in the tumour but not in the benign tissue. There was a lack of oestrogen receptors in the clear cell carcinoma but not in the polyp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…5 The occurrence of serous papillary or clear cell carcinoma confined to an endometrial polyp has been previously reported during menopause. The absence of p53 overexpression in the stroma of these tumours suggests that p53 alterations are specific to the glandular epithelium.…”
Section: Discussionmentioning
confidence: 95%
“…5 The occurrence of serous papillary or clear cell carcinoma confined to an endometrial polyp has been previously reported during menopause. The absence of p53 overexpression in the stroma of these tumours suggests that p53 alterations are specific to the glandular epithelium.…”
Section: Discussionmentioning
confidence: 95%
“…In general, EPs are benign growths with no malignant potential, although occasional cases of carcinoma can be confined to a polyp. 13 Furthermore, EPs have been associated with degeneration to carcinoma in several studies, but no real approximation has been made for this concern. Salm 4 found 4 carcinomas (0.36%) in a series with 1100 EPs, and Cohen et al 14 found 5 carcinomas (0.48%) in a population with 1034 EPs, although both were retrospective analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of representing only 5% of all endometrial adenocarcinomas, clear‐cell carcinoma is usually described as having a polypoid form, 17 which may lead to diagnostic confusion. In addition, there are reports of the occurrence of clear‐cell carcinoma in benign endometrial polyps 17–19 . The cases studied may correspond to these two possibilities.…”
Section: Discussionmentioning
confidence: 85%